Multiferroics: An Introduction - Choudhary, R N P; Patri, S K (Mesoscopic, Nanoscopic, and Macroscopic Materials (AIP Conference Proceedings Volume 1063), 2008)
Multiferroics: the multifunctional materials exhibit the entwined nature between the two distinct phenomena of ferroelectricity and ferromagnetism, which allow them to utilize for novel device concepts that would not be attainable by either ferroelectric or ferromagnetic materials. Magnetic and ferroelectric materials are time-honoured research subjects which have led to new discoveries, both scientific and technological. Multiferroic compounds are the source of magnetoelectric (ME) effects that are strong enough to induce magnetic or electric phase transitions, thus exerting ME phase control. The giant response can be generated by the presence of exceptionally large magnetic and/or electric fields in matter, which are the result of the long-range ordering. In this sense the ME effect in multiferroics is 'large' if the ME contribution corresponding to the free energy of the system is large. Due to their interesting physical, chemical, and mechanical properties, these materials have been used to realize a vast number of devices ranging from giant devices like electrical transformers to tiny devices like sensors, used in integrated circuits or as storage devices. Furthermore, these materials are likely to offer new kinds of devices and functionality, because of their size-dependent physical and chemical properties, which have motivated a lot of current research activity in the area of ferroelectric and magnetic materials. In particular, advances in atomic and nanoscale growth and characterization techniques have led to the production of modern ferroelectromagnetic materials that reveal a range of fascinating phenomena. These phenomena derived from the fact that electrons have spin as well as charge, giving an extra level of complexity to the physics, and an extra degree of freedom in device design. Magnetoelectric coupling between electric and magnetic order parameters has been theoretically predicted, and there is intense interest in its implementation in device architectures taking advantage of these properties. Multiferroics may be in the form of single-phase, exhibit mulitferroicity generally at low temperatures and in a composite form as a product property of a composite phase consisting of a magnetostrictive and a piezoelectric material. Hence, the search continues for new single-phase and composite multiferroic materials that exhibit high ordering temperatures, high coupling constant, low dielectric loss and low leakage current.